A NOVEL APPROACH OF VIROTHERAPY BASED HSF-1 shRNA IN CANCER ERADICATION - Supadmanaba, I G. P.; Wibawa-Manuaba, I. B. T. (Udayana University, 2013)
Cancer is the second leading cause of death worldwide with continues rise mortality rate. Current cancer treatment modalities are still ineffective and associated with many side effects leading to robust research to find new specific target therapy. Heat shock factor (HSF)-1 is heat shock response mediator protein and act as transcription factor for HSP encoding gene. Many cancers have up-regulated HSP as a result of increase HSF-1 expression. Interestingly, inhibition of HSF-1 has no effect to normal cell, indicating HSF-1 as promises target therapy. RNAi is potential mechanism to block and down regulate HSF-1 which will affect many cellular processes in cancer cell. Combining RNAi base treatment with oncolityc viruses will boost the therapeutic effect of this novel treatment. Despite its potency, this modality still need further research in order to evaluate its efficacy and optimal doses to gain optimal result.